Ball-milled Si powder for the production of H2 from water for fuel cell applications. (10th August 2016) - Xu, Lang; Ashraf, Sobia; Hu, Jingping; Edwards, Peter P.; Jones, Martin O.; Hadzifejzovic, Emina; Foord, John S.
Abstract: The development of a safe technique for the supply of hydrogen to small portable fuel cells has emerged as a significant barrier to their deployment in recent years, with solutions centering on the use of hydrogen absorption materials, or the generation of hydrogen through chemical reaction. In the present work we demonstrate that the ball-milling of Si under inert conditions in the presence of KOH and sucrose results in the formation of a fine Si-based powder which reacts spontaneously with water at ambient starting temperature to evolve hydrogen rapidly at high yield. Embedded KOH is capable of accelerating the hydrolysis reaction of silicon by the self-heating effect attributed to dissolution heat of KOH, obviating the need for external heating to initiate the reaction; it also reduces the sensitivity of the reaction to oxide contamination of the Si surface by enabling its dissolution in the form of soluble silicates. Moreover, the silicon–water reaction can be switched on and off by adjusting the ambient temperature. It is shown that ball-milled, KOH-embedded Si powder is able to react with different water sources, such as tap water, river water, and salt water, to produce H2 under aerobic conditions. The method represents a cheap scalable approach for the safe provision of hydrogen fuel to small fuel cells. Graphical abstract: Highlights: A simple scalable fabrication process to generate Si-based powders in the absence of oxide passivating layers is developed. The material reacts spontaneously with water to produce hydrogen in high yield. In combination with water the material this represents a viable fuel to generate hydrogen on demand for fuel cell uses.